Blood Pressure and Pulse Rate Changes in Chronic Kidney Disease Patients Before and After Hemodialysis: An Observational Study - Berlian Yuli Saputri; Ketjuk Herminaju; Manggar Purwacaraka; Yoga Resti Awalina; Hasanudin Hasanudin (Health Gate, 2026)
Background: Chronic Kidney Disease (CKD) is a progressive decline in kidney function that leads to the accumulation of metabolic waste products and excess body fluids, causing most patients to require long-term hemodialysis therapy. Hemodialysis may trigger significant hemodynamic changes, including intradialytic hypertension and tachycardia, which can cause serious cardiovascular complications. Objective: This study aimed to analyze changes in blood pressure and pulse rate before and after hemodialysis in patients with CKD at Bhayangkara Tulungagung Hospital. Methods: This study used an observational design with a before-after approach involving 30 respondents selected using a purposive sampling technique. Data were collected using structured observation sheets 15 minutes before and after each hemodialysis session. Data analysis was performed using the Wilcoxon signed-rank test with a significance level of α = 0.05. Results: Before hemodialysis, most respondents were categorized as prehypertensive (50%) with normal pulse rates (76.7%). After hemodialysis, the proportion of hypertension increased from 16.7% to 63.3%, and tachycardia increased from 16.7% to 63.3%. The Wilcoxon signed-rank test showed statistically significant changes in blood pressure and pulse rate before and after hemodialysis (p < 0.001). Conclusion: Hemodialysis was associated with significant hemodynamic changes in patients with CKD, characterized by increased proportions of hypertension and tachycardia. These findings emphasize the importance of systematic hemodynamic monitoring protocols by nurses during hemodialysis sessions to enable the early detection of cardiovascular complications and improve patient safety. Future researchers are encouraged to analyze the factors contributing to hemodynamic changes in patients with CKD